Impact of CYP3A4 and ABCB1 genetic variants on tacrolimus dosing in Greek kidney transplant recipients - Tsironi, Anna; Lazaros, Konstantinos; Mendrinou, Effrosyni; Papasotiriou, Marios; Siamoglou, Stavroula; Kydonopoulou, Kyriaki; John, Anne; Gerou, Alexandra; Gerou, Spyridon; Ali, Bassam R.; Vrahatis, Aristidis G.; Patrinos, George P. (Frontiers in Pharmacology, 2025)
BackgroundTacrolimus, an approved first-line calcineurin inhibitor, is widely prescribed in organ transplantation to prevent allograft rejection. Its narrow therapeutic index requires precise management to achieve optimal dosing and to minimize adverse drug events (ADEs) while ensuring its therapeutic efficacy. Among several factors, genetic differences contribute significantly to the inter-individual and inter-ethnic variability in pharmacokinetics (PK) of tacrolimus in kidney transplant recipients. As a result, investigating the role of genetic variation in Greek transplant recipients becomes crucial to optimizing therapeutic strategies and enhancing the efficacy of immunosuppressive treatment.HypothesisGenetic variants which are known to influence the activity of enzymes or drug-transporters critical to tacrolimus pharmacokinetics, may significantly affect the required kidney post-transplant tacrolimus daily dose.AimTo assess the correlation of ABCB1 genetic variants (rs1128503, rs2229109) and CYP3A4 (rs2242480, rs4986910) with tacrolimus dose-adjusted trough concentration (C0/D), in Greek kidney transplant recipients.MethodsNinety-four unrelated Greek kidney transplant recipients were included in this study from the Department of Nephrology and Kidney Transplantation of the University General Hospital of Patras. Patients’ dose-adjusted trough levels were measured at five distinct time points after transplantation and analyzed in relation to the possible influence of CYP3A4 and correlated with the abovementioned ABCB1 genetic variants using standard genotyping analysis and Sanger sequencing.ResultsThe genetic variants rs1128503, rs2229109, rs2242480, rs4986910 did not show any significant association with the daily dosing requirements of tacrolimus for at least 1 year, in Greek patients who have undergone kidney transplant.ConclusionIt remains uncertain whether these genetic variants influence the assessment of the appropriate tacrolimus dosing 1 year after transplantation in Greek kidney transplant recipients.